A valence-based account of group interaction and decision making. Issue 2 (3rd April 2022) - Bonito, Joseph A.; Keyton, Joann
ABSTRACT: Group participants often develop a range of problem solutions before discussion. We addressed whether, and at what level of analysis, initial opinions influence discussion and perceptions of decision outcomes. The Group Valence Model (GVM) presents a dual-process approach to interaction and decision making as a function of the distribution of supportive and oppositional comments. GVM predicts that discussion reflects individual-level opinions until a group solution emerges, whereupon discussion is influenced by group-level factors. Data from four previous studies were machine-coded for supportive and oppositional statements. Results indicated that the model holds in some degree at the group level but not at the individual level. Discussion focuses on mechanisms that drive interaction prior to the emergence of a group-level solution.